2016
DOI: 10.5296/ijrd.v3i2.9194
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Smallholder Crop Diversification: A Case Study of Manicaland and Masvingo Provinces in Zimbabwe

Abstract: This study analyzes the degree of crop diversification and factors associated with crop diversification among 479 smallholder farmers in Manicaland and Masvingo provinces of Zimbabwe household, education, number of livestock units, access to irrigation, membership to a farmers group, access to markets, farming experience, farms on flat terrain, farmer to farm extension, routine extension, agro-ecological zone and household income are significant contributors to increasing crop diversification. In turn, crop sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
3
13
2
4
Order By: Relevance
“…Higher ddp enhances capacity to save and invest. This raises risk taking capacity of farmers (Joshi et al 2004;Rao et al 2004;Gulati et al 2005;Dube & Guveya 2016). However, contrary to these we observe that ddp is higher for relatively backward districts indicating the phenomenon that crop diversification may be distress-driven, as in the absence of alternative employment avenues farmers in underdeveloped regions may resort to multiple farming for sustenance.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Higher ddp enhances capacity to save and invest. This raises risk taking capacity of farmers (Joshi et al 2004;Rao et al 2004;Gulati et al 2005;Dube & Guveya 2016). However, contrary to these we observe that ddp is higher for relatively backward districts indicating the phenomenon that crop diversification may be distress-driven, as in the absence of alternative employment avenues farmers in underdeveloped regions may resort to multiple farming for sustenance.…”
Section: Discussioncontrasting
confidence: 56%
“…We have taken district domestic product per capita as a proxy for district income, and per capita district domestic product from agriculture (ddp) as a proxy for agricultural income. We expect a positive effect of agricultural income on diversification as has also been shown in some other studies (Joshi et al 2004;Rao et al 2004;Gulati et al 2005;Dube & Guveya 2016). In order to smoothen the data, we have taken log transformation of ddp (i.e., lnddp) as a determinant of diversification.…”
Section: Agricultural Income (Ddp)mentioning
confidence: 77%
“…The positive and statistically significant coefficient implies that male-headed households or farms are more likely to participate in non-rice crop production. This finding is consistent with Sichoongwe et al (2014) and Dube & Guveya (2016). Although gender identity can significantly increase the likelihood of diversification, it cannot enhance the extent of diversification as the coefficient of gender identity of the household head is negative and insignificant.…”
Section: Resultssupporting
confidence: 82%
“…Searching for the factors of this tendency in different studies has found that household income, trade experience, household membership in a farmers’ association, household size, farmer’s education, farming experience, number of livestock and land ownership are widely identified as the major catalysts of crop diversification (Ashfaq et al, 2008; Benin et al, 2003; Birthal et al, 2007; Dube & Guveya, 2016; Mahmud et al, 1994; Metzel & Ateng, 1993; Mussema et al, 2013; Rahman, 2009a; Rehan, 2020; Sichoongwe et al, 2014). Although the availability of irrigation can be anticipated as one of the crucial factors to diversifying the portfolio, Rahman (2008) has found that irrigation encourages the farms in Bangladesh to cultivate mostly HYV rice crops instead of non-rice crops.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Herfindahl index originated in the marketing industry to measure the extent of dispersion and concentration of activities at a given time. It has also been widely employed in the literature on agricultural specialization (Dube & Guveya, 2016; El Benni et al., 2012; Ogundari, 2013; Rahman, 2009). This specialization index ranges from 0 to 1, with a value approaching 1 when specialization is increasing and tends toward 0 as households’ production is diversified.…”
Section: Methodsmentioning
confidence: 99%